Cytological and histochemical examination of bovine endometrium during sexual life - ΠΑΠΑΔΟΠΟΥΛΟΣ, XP. (Journal of the Hellenic Veterinary Medical Society, 2019)
In the present study the author is dealing with the changes in the endometrium of the cow, from histological and histochemical point of view, during the sexual life. Forty cows, during the main stages of sexual activity, were used and the different phases were determined accurately, by history of the animals and the examination of genital organs. The whole uterus was removed immediately after slaughter and standard samples were taken from both the caruncular and intercaruncular areas as from the cervix, and, were used for histological and histochemical examination. The histological changes and the enzymatic activity in the endometrium are represented in the quoted microphotographes and in the table I, and reported in detail in discussion.